A multi-step approach to develop a “storytelling” intervention to improve patient gout knowledge and improve outpatient follow-up - Lesley E. Jackson; Kenneth G. Saag; Germán Chiriboga; Stephenie C. Lemon; Jeroan J. Allison; Amy Mudano; Giovanna Rosas; Phillip J. Foster; Maria I. Danila (Contemporary Clinical Trials Communications, 2023)
Background: “Storytelling” interventions influence knowledge, attitudes and behavior to promote chronic disease management. We aimed to describe the development of a video “storytelling” intervention to increase gout knowledge and promote adherence to medications and follow-up care after an acute gout flare visit in the emergency department. Methods: We developed a direct-to-patient storytelling intervention to mitigate modifiable barriers to gout care and promote outpatient follow-up and medication adherence. We invited adult patients with gout as storytellers. We utilized a modified Delphi process involving gout experts to identify key themes to guide development of an intervention. Using a conceptual model, we selected stories to ensure delivery of evidence-based concepts and to maintain authenticity. Results: Our video-based storytelling intervention consisted of segments addressing modifiable barriers to gout care. Four diverse gout patients were recruited as storytellers and interviewed with questions that covered gout diagnosis and care. Eleven international gout experts from diverse geographic locations generated and ranked items they considered important messages to promote outpatient gout care follow-up and treatment adherence. Filmed videos were truncated into segments and coded thematically. Distinct segments that captured desired messages were combined to form a cohesive narrative story based on gout patient experiences that conveyed evidence-based strategies to manage gout. Conclusions: Using the Health Belief Model, we developed a culturally appropriate narrative intervention containing “storytelling” that can be tested as an approach to improve gout outcomes. The methods we describe may be generalizable to other chronic conditions requiring outpatient follow-up and medication adherence to improve outcomes.